2022
DOI: 10.3389/fnins.2022.1093850
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study of neuropsychological scores of infant patients with cobalamin C defects and influencing factors of cerebral magnetic resonance imaging characteristics

Abstract: PurposeThe purpose of this study was to investigate whether baseline cerebral magnetic resonance imaging (MRI) characteristics could predict therapeutic responsiveness in patients with cobalamin C (cblC) defects.Materials and methodsThe cerebral MRI results of 40 patients with cblC defects were evaluated by a neuroradiologist. Neuropsychological scores and imaging data were collected. Neuropsychological tests were performed before and after standardized treatment.ResultsThirty-eight patients initially underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Diffuse white matter swelling, severe leukoaraiosis of varying degrees, hydrocephalus, corpus callosum atrophy, and symmetric bilateral lesions of the basal ganglia are frequent and distinctive imaging findings in early-onset cblC disease. However, late-onset cases often exhibit cerebral atrophy and patchy lesions in the deep white matter (17)(18)(19). Cerebellar involvement is uncommon in cblC disease, and literature review reveals only seven reported cases with cerebellar symptoms or imaging changes (12,16,18,(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse white matter swelling, severe leukoaraiosis of varying degrees, hydrocephalus, corpus callosum atrophy, and symmetric bilateral lesions of the basal ganglia are frequent and distinctive imaging findings in early-onset cblC disease. However, late-onset cases often exhibit cerebral atrophy and patchy lesions in the deep white matter (17)(18)(19). Cerebellar involvement is uncommon in cblC disease, and literature review reveals only seven reported cases with cerebellar symptoms or imaging changes (12,16,18,(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%